2010
DOI: 10.1074/jbc.m109.056523
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α Regulates Transforming Growth Factor-β-dependent Epithelial-Mesenchymal Transition by Promoting Hyaluronan-CD44-Moesin Interaction

Abstract: Aberrant epithelial-mesenchymal transition (EMT) is involved in development of fibrotic disorders and cancer invasion.Alterations of cell-extracellular matrix interaction also contribute to those pathological conditions. However, the functional interplay between EMT and cell-extracellular matrix interactions remains poorly understood. We now show that the inflammatory mediator tumor necrosis factor-␣ (TNF-␣) induces the formation of fibrotic foci by cultured retinal pigment epithelial cells through activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
154
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(162 citation statements)
references
References 63 publications
8
154
0
Order By: Relevance
“…TNF-α regulates TGFβ-promoted epithelial mesenchymal transition (EMT) by inducing HA-CD44-moesin interaction (Takahashi et al, 2010), suggesting transactivation of TGFβRI by TNF-α. We hypothesized that HA would activate TGFβ receptor signaling to induce expression of PAI-1.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α regulates TGFβ-promoted epithelial mesenchymal transition (EMT) by inducing HA-CD44-moesin interaction (Takahashi et al, 2010), suggesting transactivation of TGFβRI by TNF-α. We hypothesized that HA would activate TGFβ receptor signaling to induce expression of PAI-1.…”
Section: Discussionmentioning
confidence: 99%
“…In different cell types, the binding is mediated by various linker proteins like ERM (ezrin, radixin, moesin, merlin), ankyrin, and IQGAP (1,46,58,(61)(62)(63)(64)(65) (Fig. 7A).…”
Section: Regulation Of Cd44 Expression and Phosphorylation By Il-1␤-imentioning
confidence: 99%
“…Additionally, 4-MU effects a pronounced reduction of HA synthase 2 (HAS2) transcription but by mechanisms that are currently unknown (32)(33)(34). As a potent inhibitor of HA, 4-MU has been used to examine the role of HA in epithelial-mesenchymal transitions (35), collagen-induced arthritis (36), invasion and metastasis of osteosarcoma (37) and breast cancer cells (38), inflammation and autoimmunity (31), chondrogenic differentiation (39), myofibroblast differentiation (40,41), and keratinocyte activation (42). We have shown that 4-MU blocks the assembly of pericellular coats on bovine, rat, and mouse chondrocytes and diminishes the responsiveness of chondrocytes to bone morphogenetic protein-7 similar to results obtained by hyaluronidase treatment (43).…”
mentioning
confidence: 99%